Rasio Keuangan Sebagai Dasar Penilaian Kinerja Keuangan Pada KPN Dharma Wiguna Denpasar - Kurniawan, Denny Kristiadi; Lestari, Putu Vivi (E-Jurnal Manajemen, 2014)
Abstract Existence of cooperation is to improve member prosperity especially and public prosperity generally and follow to develop arrangement of national economic. This study was to analyze financial performance in the Civil Servant Cooperation of Dharma Wiguna of Denpasar City in 2007-2011. Based on ratio of financial that based on the cooperation and small and medium business ministry of the Republic of Indonesia No. 06/Per/M.KUKM/V/2006 hence financial performance of civil servant cooperation of Dharma Wiguna of Denpasar city in 2007-2011 it can be seen from its liquidity in good category, the solvability is less, its profibility in good category and its efficiency is less. The result of index analysis shown its liqudity tend to increase, its solvability tend to decrease, its profitability tend to increase and its efficiency tend to decrease. Keywords: financial performance, financial ratio
Keywords: financial performance, financial ratio